1973
DOI: 10.1159/000230970
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Allergens of Horse Dandruff and Horse Serum

Abstract: Serum albumin was found to be an important allergen in horse epithelia extracts. The albumin concentration varied considerably, depending on the raw material used for the preparation of the allergen extracts. In addition to serum albumin, two allergenic proteins were demonstrated in horse dandruff. The molecular weights of these allergens were calculated to be about 38,000 and 22,000, respectively. The pi of the latter was 4.2. Fifty sera from allergic patients were studied by means of the radioallergosorbent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 3 publications
2
24
0
3
Order By: Relevance
“…Immunoelectrophoretic and immunodiffusion analysis showed the presence of cat serum albumin. This serum protein could be responsible on the allerginicity of this frac tion and numerous reports indicate that albumin is an important allergen in horse [11] and dog [12] epithelia and to a lesser extent in cat extracts [2,4], The fraction with a mean molecular weight of 40.000 was resolved in two peaks of activity. One of them was associated with the protein band of pi 3.5.…”
Section: Discussionmentioning
confidence: 92%
“…Immunoelectrophoretic and immunodiffusion analysis showed the presence of cat serum albumin. This serum protein could be responsible on the allerginicity of this frac tion and numerous reports indicate that albumin is an important allergen in horse [11] and dog [12] epithelia and to a lesser extent in cat extracts [2,4], The fraction with a mean molecular weight of 40.000 was resolved in two peaks of activity. One of them was associated with the protein band of pi 3.5.…”
Section: Discussionmentioning
confidence: 92%
“…Serum-related proteins in complex epithelial extracts were identified by using horse albumin and horse serum as markers in certain assays. In addition to previous studies [4,10,11 ] on horse epithelial extracts we extended our in vestigations to more recently developed methods, e.g. size exclusion high-performance liquid chromatogra phy (SE-HPLC) and immunoblotting methods.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid ambiguous diagnostic results [6][7][8] or strong differences in allergenic activity between al lergen extracts from horse epithelia [9][10][11] not only the methods used for the extraction but also the source and the manufacturing process of the raw ma terial itself should be harmonized.…”
Section: Introductionmentioning
confidence: 99%
“…The major horse allergen, Equ c1, is a potent allergen responsible for about 80% of anti-horse IgE antibody response in patients who are chronically exposed to horse allergens. Although much work has been carried out on the isolation and identification of the horse allergenic agents responsible for human hypersensitivity response (12)(13)(14)(15)(16), the major horse allergen was only recently purified from hair and dandruff (17). A previous study by SDS-polyacrylamide gel electrophoresis (SDS-PAGE) and isoelectric focusing-PAGE showed that Equ c1 appears as a single polypeptide with a relative molecular mass of 21,500 daltons and a pI of 3.9.…”
mentioning
confidence: 99%